Internalizing Animal Welfare Norms: Legal Frameworks for Protecting Animals from Mistreatment - Setiabudhi, Donna Okthalia; Irwansyah, Irwansyah; Yunus, Ahsan (Universitas Lampung, 2023)
This study examines the critical dimensions of animal welfare, focusing on the impact of various situations and environments on animals from their perspective. Neglecting animal welfare, especially for livestock and slaughter animals, can lead to fear, stress, and pain during essential processes such as transportation, marketing, and inadequate provision of feed and water. Utilizing a socio-juridical approach, the research centers on North Sulawesi Province, where certain animal slaughter practices have been criticized for their cruelty on an international scale. The findings suggest that effective animal protection to ensure welfare can be realized through the establishment of specific laws and regulations that comprehensively address animal protection issues. Such regulations are necessary to prevent legal disharmony and mitigate multiple interpretations by enforcement officials. Moreover, it is crucial to recognize animals as subjects capable of transmitting diseases rather than mere objects of disease transmission, particularly concerning zoonotic infections affecting humans. In Indonesia, the primary factors contributing to inadequacies in animal protection include insufficient sanctions for violations and a lack of knowledge and understanding among law enforcement officials.